Studies on bifunctional Fe(ii)-triazole spin crossover nanoparticles: time-dependent luminescence, surface grafting and the effect of a silica shell and hydrostatic pressure on the magnetic properties1. Issue 30 (14th August 2015) - Herrera, Juan Manuel; Titos-Padilla, Silvia; Pope, Simon J. A.; Berlanga, Isadora; Zamora, Félix; Delgado, Juan José; Kamenev, Konstantin V.; Wang, Xiao; Prescimone, Alessandro; Brechin, Euan K.; Colacio, Enrique
<x xml:space="preserve">Abstract</x> SiO2-coated Fe-triazole spin-crossover nanoparticles were functionalized with dansyl luminophores.